THE GROSS MOTOR ABILITY PROFILE OF GRADE V STUDENTS IS BASED ON THE GEOGRAPHICAL CONDITIONS OF THE COASTAL AREA AT SDN 003 SERI KUALA LOBAM, BINTAN REGENCY, RIAU ISLANDS PROVINCE - Ghea Ardila Wibowo; Oca Fernandes AF; Siti Maesaroh (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to find out the extent of gross motor skills of grade 5 elementary school students in SDN 003 Seri Kuala Lobam. The researcher took research samples at the school location in the coastal area. According to local elementary school teachers and also the results of researchers' observations over the years, there are differences in the development of both academic and non-academic elementary school students between areas adjacent to the sea and those that are not. including in his gross motor development. Motor development is very necessary for children's development, especially in school. gross motor is a skill that requires coordination of a large part of the child's body. Based on the above opinion, it is concluded that gross motor is a physical movement activity that requires coordination of the limbs by using their large muscles. Students who have good motor skills are able to do sports skills than students who have fission skills. From the explanation above, the researcher wants to conduct research on the Gross Motor Ability Profile of students, where this is the main focus because Gross Motor Skills is very important to be mastered by a person because he can do daily activities, without having good movements he will lag behind others, such as: running, jumping, pushing, throwing, catching, kicking and so on, these activities require and use large muscles in a person's body